Pengembangan Buku Ajar Bahasa Inggris 3 dengan Materi English For Specific Purposes (ESP) untuk Teknik Informatika Semester III Universitas Pamulang - Darmawati Darmawati; Mohadib Mohadib; Sulasih Sulasih (Faculty of training and education, Pamulang university, 2022)
The purpose of developing English language materials 3 is to achieve learning targets in accordance with KKNI standards for teaching English outside the English department, namely English for specific purposes. The development of textbooks for English courses 3 with English content for specific purposes will include information technology that will help students learn independently with the support of mobile assisted language learning. These materials will help students develop 4 skills in English, namely, reading, speaking, listening and writing. This study uses research and development (R&D) method, where the final product is an ISBN textbook for English courses 3. The steps of this research go through 6 stages, namely ; first, collect initial data, then plan the product, then carry out initial product development, the next stage is to conduct initial trials, then make several revisions to the book content, and conduct field tests. The 3rd semester students of the Informatics Engineering Study Program at Pamulang University in 2020/2021 are the subjects of this research.Keywords: Development; teaching materials; English for Specific Purposes; technology